(untitled) (Research, Society and Development, 2022)
The early benefit protocol in orthognathic surgery or surgery-first approach (SFA) has as its main idea the surgical approach before previous orthodontic preparation, in contrast to the idea of ​​the traditional approach, which advocates a preoperative orthodontic treatment, which may present more uncomfortable for the patient when compared to surgery-first because it takes a very long time, discomfort during the orthodontic treatment, and the patient may present psychosocial problems related to the delay in the resolution of the main complaint and/or even the aggravation of such complaint due to attenuation of facial asymmetry resulting from the correct position of the teeth in the arches, and possible intra-oral complications related to hygiene and oral health with the use of intra-oral orthosis. The surgery-first approach is based on initially improving facial aesthetics, which is usually the patient’s main complaint, and then moving on to the second stage of occlusal movement and alignment. This literature review aims to evaluate and compare the findings regarding the conventional protocol. and the suggestion-first protocol. A MEDLINE search. Inclusion criteria were 1) human study and 2) orthognathic surgery with surgical-first approach or equivalent, and 3) three-dimensional planning with virtual flow in a suggestion-first approach. After an evaluation of the contemporary literature, it was concluded that this approach is positive when related to treatment time, patient’s quality of life, post-surgical orthodontic time and occlusal stability. Overall, the SFA achieved optimal results comparable to the conventional protocol regarding treatment success.